PENGARUH KEMASAN DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN SUSU KENTAL MANIS FRISIAN FLAG (Studi Pada Konsumen Susu Kental Manis Frisian Flag di Giant Maspion Square Surabaya) - NUR WENY, INDAHING (Jurnal Ilmu Manajemen (JIM), 2018)
One of the companies that issued condensed milk products is PT Frisian Flag Indonesia under the brand of condensed milk Frisian Flag. Condensed milk Frisian Flag is condensed milk with market share and the highest brand value among its competitors. This research is based on the phenomenon of gab, the gap when condensed milk Frisian Flag is a brand with top of mind advertising in Indonesia and the most packaging variants but in each year experienced a decline in sales that inversely proportional to the market share continues to increase. The purpose of this study was to examine and analyze the effect of packaging and advertising appeal towards the purchase decision Frisian Flag condensed milk. This study is a conclusive study. And using non probability sampling techniques. The sample taken as many as 210 respondents. Data collection techniques using questionnaires. The measurement scale in this study uses a Likert scale. Then analyzed using multiple linear regression technique. The results showed that the effect of packaging and advertising appeal on purchase decision Frisian Flag condensed milk. The variable of packaging and advertising appeal that can be explained by the purchase decision variable is 74.2%. Keywords: packaging, advertising appeal, purchase decision.